2014
DOI: 10.11607/jomi.3382
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Accuracy of Plastic Transfer Impression Copings for Three Implant Systems

Abstract: This assignment applies to all translations of the Work as well as to preliminary display/posting of the abstract of the accepted article in electronic form before publication. If any changes in authorship (order, deletions, or additions) occur after the manuscript is submitted, agreement by all authors for such changes must be on file with the Publisher. An author's name may be removed only at his/her written request. (Note: Material prepared by employees of the US government in the course of their official d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 23 publications
0
8
0
1
Order By: Relevance
“…One clinical 12 study and 4 in vitro 21‐24 studies from the completely edentulous and one clinical 11 and one in vitro 25 study from the partially edentulous group were excluded from the meta‐analysis, which included 11 studies overall. Excluded studies 26‐62 and reasons for exclusion are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…One clinical 12 study and 4 in vitro 21‐24 studies from the completely edentulous and one clinical 11 and one in vitro 25 study from the partially edentulous group were excluded from the meta‐analysis, which included 11 studies overall. Excluded studies 26‐62 and reasons for exclusion are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…[7][8][9] Variables that have been shown to influence implant impression accuracy include impression material selection, [10][11][12] tray selection, 13 impression approach, 9,14 implant angulation, 15,16 and the inherent fit of impression components. 17,18 While numerous studies have evaluated and compared existing implant impression techniques, research to date does not support one single impression technique as superior to all others. 9 The advent of digital technology gives clinicians the option to use intraoral scanners in place of conventional impression techniques.…”
mentioning
confidence: 99%
“…Passivity is a concern with multiple implants placed at varying angulations to each other because of documented inaccuracies in implant impressions and in restoration manufacturing procedures [5] . The accuracy of an implant cast depends on many factors: the impression material, impression technique, angulation at which the implant is placed, accuracy of dental stone and master cast technique [15,16,21] . With the use of implants having an internal connection there is a reported decrease in the accuracy of impressions with an increase in the angulation of implants [22] .…”
Section: Discussionmentioning
confidence: 99%